Region splitting-based resource partitioning to enhance throughput in long term evolution - Advanced networks. (October 2018) - Ezhilarasi, S.; Bhuvaneswari, P.T.V.
Abstract: In Long Term Evolution-Advanced networks, efficient resource partitioning is needed for improving throughput for User Equipment (UE). In this research, a region splitting-based resource partitioning scheme is proposed for enhancing the throughput of indoorMacro UE (MUE). The macrocell is divided into three regions, namely, the inner, centre and outer regions. The femtocells present in each region share the resources of the corresponding macrocell. The spectrum is partitioned into four non-overlapping sub-bands. These sub-bands are assigned to a cluster of three cells for mitigating cross-tier interference. The throughput of indoorMUE which is located at the boundary of inner region is analysed with respect to various numbers of femtocells and, MUE devices, angles made by MUE devices and femtocell transmission power. The proposed scheme has been compared with a fractional frequency reuse scheme in terms of inner-region radius. The inference drawn is that a maximum throughput enhancement of 29.7% has been achieved.